Strategi Flower Writing untuk Meningkatkan Kemampuan Menulis Mahasiswa Program Studi Teknik Informatika - Nadiyatul Uswatun Hasanah; Aminatuz Zuhriyah (CV. ITTC INDONESIA, 2026)
Writing is one of the essential academic competencies that university students are expected to master, including those enrolled in non-language study programs. However, preliminary observations conducted among second-semester students of the Informatics Engineering Study Program at Yudharta University revealed that many students experienced difficulties in generating main ideas, developing supporting details, organizing coherent paragraphs, and applying appropriate grammar and vocabulary. These problems contributed to the low quality of their English writing. Therefore, this study aimed to improve students' writing skills through the implementation of the Flower Writing Strategy. This research employed Classroom Action Research (CAR) consisting of three cycles, each involving planning, action, observation, and reflection stages. The participants were 33 second-semester Informatics Engineering students enrolled in the English course. Data were collected through classroom observations, field notes, documentation, and writing tests. The collected data were analyzed using descriptive comparative analysis by comparing students' performance across the three research cycles. The findings demonstrated a consistent improvement in students' writing performance after the implementation of the Flower Writing Strategy. The mean writing score increased from 77 in Cycle I to 79 in Cycle II and reached 83 in Cycle III. Besides the improvement in writing scores, classroom observations revealed increased student participation, better idea development, improved paragraph organization, more accurate vocabulary use, and fewer grammatical errors. The visual graphic organizer used in the Flower Writing Strategy also enabled students to organize their ideas more systematically during the pre-writing stage. In conclusion, the Flower Writing Strategy proved effective in improving the English writing skills of EFL students and can be recommended as an alternative instructional strategy for teaching writing in non-language higher education programs.